Reformulation of Regional Administrative Law: A Study of Civil Servant Dispute Resolution in Local Government - Ferika Nurfransiska; Dairani, Dairani; Yosep Heristyo Endro (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2025)
Civil service disputes within local governments are crucial issues that require an appropriate legal approach within the framework of state administrative law. In practice, the resolution of these disputes is often hampered by regulatory weaknesses and disharmony between the central and regional authorities. This study aims to analyze the characteristics of local administrative law related to civil service management, strengthen administrative law norms, and evaluate dispute resolution mechanisms. This study uses a normative juridical approach and literature review, focusing on the importance of synergy between the ASN Law, Government Administration Law, and regional regulations to create a fair, effective, and efficient dispute resolution system. This study found that the lack of clarity in authority and administrative procedures at the regional level hinders the resolution of ASN disputes. There is disharmony between the ASN Law, the Government Administration Law, and their implementing regulations, which weakens the role of the KASN and PTUN as institutions that guarantee administrative justice. In addition, limited institutional capacity and human resources in local government hinder the substantive implementation of administrative laws. [Sengketa kepegawaian di lingkungan pemerintah daerah merupakan isu krusial yang membutuhkan pendekatan hukum yang tepat dalam kerangka hukum administrasi negara. Dalam praktiknya, penyelesaian sengketa ini sering terhambat oleh kelemahan regulasi dan disharmoni antara kewenangan pusat dan daerah. Artikel ini bertujuan untuk menganalisis karakteristik hukum administrasi daerah yang berkaitan dengan pengelolaan kepegawaian, penguatan norma hukum administrasi, serta mengevaluasi mekanisme penyelesaian sengketa. Penelitian ini menggunakan pendekatan yuridis normatif dan studi literatur, dengan fokus pada pentingnya sinergi antara UU ASN, UU Administrasi Pemerintahan, dan peraturan daerah untuk menciptakan sistem penyelesaian sengketa yang adil, efektif, dan efisien. Penelitian ini menemukan bahwa lemahnya kejelasan kewenangan dan prosedur administratif di tingkat daerah menjadi faktor pemghambat penyelesaian sengketa ASN. Terdapat disharmonisasi antara UU ASN, UU Administrasi Pemerintahan, dan peraturan pelaksanaannya melemahkan peran KASN dan PTUN sebagai institusi penjamin keadilan administrasi. Selain itu, keterbatasan kapasitas kelembagaan dan sumber daya manusia di pemerintah daerah menghambat implementasi hukum administrasi secara substantif].